EDUCATION ON SAFE, HEALTHY AND NUTRITIOUS FOOD THROUGH THE PRACTICAL MODULE NUTRITION GOES TO SCHOOL (NGTS) AT SMAN 1 BEBER AND IIBS SD/SMP FAJAR HIDAYAH, CIREBON REGENCY - Uun Kunaepah; Wiwit Estuti; Isnar Nurul Alfiyah (Jurnal Abdisci, 2024)
School is a convenient place for learning and character formation of students. Education in school greatly influences knowledge, attitudes, and behaviors of consumption and choosing food. School is a place to teach, socialize, and apply good habits because most children spend their time at school. Education about healthy food is critical so that it becomes a good habit in the future. The role of teachers and parents at this time is significant. Nutrition Goes To School (NGTS) is a SEAMEO Recfon Program that promotes healthy canteens and school nutrition gardens. The Healthy Canteen and School Nutrition Garden are part of health education in schools. Educational institutions must be able to present and provide healthy canteens, as well as healthy food and school nutrition gardens, as one of the services that schools must provide to realize intelligent and healthy children. The method of implementing this practical module begins with the creation of an NGTS practical module by the Community Service Team, followed by socialization activities, training (TOT) for implementing practical modules, mentoring, and evaluation. This Community Service activity continues the NGTS carried out in 2019 at government-owned elementary and junior high schools. In 2022, we will try to make a practical NGTS module and apply it to high school and elementary/junior high school with the hope that education about Nutrition can be applied at all age stages from elementary to high school, both in government-owned and privately owned schools.